ChemInform Abstract: Synthesis, Characterization, and Antibacterial Activity of Novel Pyridones. Issue 38 (10th September 2014) - Gezegen, Hayreddin; Ceylan, Mustafa; Karaman, Isa; Sahin, Ertan
Abstract Novel pyridone derivatives (IV) and (V) are synthesized by cyclization of adducts of diethylmalonate to chalcone with ammonium acetate in two different solvent systems.